Use the force-responsibly. (Economist, 2023)
The author reflects on the need for state or government-sponsored hackers to be responsible for their cyberwar attacks to avoid significant collateral damages. Also cited are the alleged irresponsible cyberwar launched by Russian hackers during the invasion of Ukraine that adversely affected nearly 6,000 wind farms in Germany, and Great Britain's National Cyber Force's (NCF) recommendations on how to responsibly use cyber power.